Volviendo a pensar sobre el final del Complejo de Edipo. - Zonis, Adolfo Miguel (Psicoanálisis: Revista de la Asociación Psicoanalítica de Buenos Aires, 2024)
In the psychoanalytic language, there is a polysemy that requires, in every exchange, to clarify the terms that are being used. In this case, so as to rethink about the ending of the Oedipus Complex, I found it relevant to highlight which aspect of the work of Sophocles is taken by Freud for its conceptualization, what he means by "complex", "phallus", "castration anxiety" and "primal repression". From that point on, I describe different points of view about the significant process of this stage of the children's life, by concluding in my own summary, supported by the Freudian conceptualization that: Each normal person is that only on average, their ego is close to the one of a psychotic in this or that part, to a greater or lesser degree. After this analysis I find it necessary to add that, although Freud designed a theory and a technique for the clinical practice of the neurosis, these remain as current contributions, even though the psychoanalysis broadened its operational field in the narcissism territory also based on Freudian postulates, not only with the theorization about narcissism, but also and especially in 1920 with "Beyond the Pleasure Principle" and "The Splitting of the Ego in the Process of Defence" (1938). In order to comprehend all of this clinical practice, the theorization of the Oedipus Complex, (which has been modified by other authors) continue to be indispensable, as well as the post Freudian developments. Only with Freud it is not enough, without Freud it is impossible.